Once-daily maraviroc versus tenofovir/emtricitabine each combined with darunavir/ritonavir for initial HIV-1 treatment. (15th May 2016) - Stellbrink, Hans-Jürgen; Le Fevre, Eric; Carr, Andrew; Saag, Michael S.; Mukwaya, Geoffrey; Nozza, Silvia; Valluri, Srinivas Rao; Vourvahis, Manoli; Rinehart, Alex R.; McFadyen, Lynn; Fichtenbaum, Carl; Clark, Andrew; et al.
Abstract : Objective: The aim of this study was to evaluate the efficacy of maraviroc along with darunavir/ritonavir, all once daily, for the treatment of antiretroviral-naive HIV-1 infected individuals. Design: MODERN was a multicentre, double-blind, noninferiority, phase III study in HIV-1 infected, antiretroviral-naive adults with plasma HIV-1 RNA at least 1000 copies/ml and no evidence of reduced susceptibility to study drugs. Methods: At screening, participants were randomized 1 : 1 to undergo either genotypic or phenotypic tropism testing. Participants with CCR5-tropic HIV-1 were randomized 1 : 1 to receive maraviroc 150 mg once daily or tenofovir/emtricitabine once daily each with darunavir/ritonavir once daily for 96 weeks. The primary endpoint was the proportion of participants with HIV-1 RNA less than 50 copies/ml (Food and Drug Administration snapshot algorithm) at Week 48. A substudy evaluated bone mineral density, body fat distribution and serum bone turnover markers. Results: Seven hundred and ninety-seven participants were dosed (maraviroc, n = 396; tenofovir/emtricitabine, n = 401). The Data Monitoring Committee recommended early study termination due to inferior efficacy in the maraviroc group. At Week 48, the proportion of participants with HIV-1 RNA less than 50 copies/ml was 77.3% for maraviroc and 86.8% for tenofovir/emtricitabine [difference of −9.54% (95% confidence interval: −14.83 to −4.24)]. More maraviroc participants discontinued for lack of efficacy, which was not associated with non-R5 tropism or resistance. Discontinuations for adverse events, Category C events, Grade 3/4 adverse events and laboratory abnormalities were similar between groups. Conclusion: A once-daily nucleos(t)ide-sparing two-drug regimen of maraviroc and darunavir/ritonavir was inferior to a three-drug regimen of tenofovir/emtricitabine and darunavir/ritonavir in antiretroviral-naive adults. Abstract : Supplemental Digital Content is available in the text